Pembinaan Fiqh Haid Pra-Remaja Untuk Menguatkan Tafaqquh Fi Ad Din Bagi Siswi Madrasah Ibtidaiyah Muhammadiyah Kartasura - Alfiyatul Azizah; Anisa Nur Izzati; Emma Muthia Lathifah; Fahmi Ikhlasul Amal; Muhammad Rizqi Nashrudin; Naadiyah Syifaul Ummah; Nabila Zakiyah; Zakiyah Laili Maghfiroh (TAAWUN, 2024)
This community service aims to provide effective guidance and assistance for pre-adolescent students regarding the concept of women's blood in Islam and from a health perspective. This activity targets students to understand conceptually and be able to apply it in everyday life. Therefore, this community service program is implemented using the Participatory Action Research (PAR) method so that there is effective cooperation and reciprocity between the PKM team and partners. After providing conceptual material, the PKM team also assisted in practically applying the material in the school environment. The target of this program is female students in grades 3-6 of MIM Pucangan Kartasura. The dissemination of material is carried out in stages and uses fun learning media in the form of educational videos, direct practice, and periodic mentoring. Meanwhile, the material taught is; the jurisprudence of water for purification, female reproductive anatomy, knowledge about menstruation, the color and texture of menstrual blood, the jurisprudence of menstruation, the differences between menstruation, childbirth and menstruation, and procedures for using sanitary napkins correctly and by the Shari'a. The implementation of this PKM showed an encouraging impact for partners, this can be seen from the activeness and positive responses of participants in all sessions. The success of this PKM activity is also demonstrated by high post-test results and practical applications, which are evaluated periodically to indicate the participant's mastery of the material and the assistance provided.